Every Member of Your Team is a Salesperson - Blachford, Pauline (Canadian Journal of Optometry, 2017)
In my two decades working on the business side of this industry, I’ve seen how it can be a challenge for small, independent optometry practices to employ a full-time optician to oversee eyewear sales. Even at larger practices where there may be several opticians, it can be a struggle to significantly increase sales without a proper[...]